Using taxation to control Tobacco consumption in Uganda - Ntale, Anita; Kasirye, Ibrahim (Economic Policy Research Centre, 2018)
This brief explores the trends in tobacco taxation in Uganda and highlights the importance of addressing factors that contribute to affordability when using taxation as a tobacco control tool. Drawn from a recent study by EPRC which simulates the potential impact of different tax changes on tobacco consumption, the brief underscores the need to make regular, consistent and uniform adjustments to the tobacco tax structure.